PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS KINERJA KARYAWAN DI UD. BALI SUNSRI CELUK SUKAWATI - Ni Nyoman Wina Puspasari; Tiara Kusuma Dewi; Laras Oktaviani (Journal Research of Accounting, 2021)
This study aims to determine how the influence of accounting information systems and internal control systems of employee performance. The population in this study are employees of UD. Bali Sunsri. Total samples that fill the questionnaire of this research amounted to 62 people consisting of employees who work by using accounting information system that is, manager, finance and cashier and without it like the silver smith and photografer. The results of this study indicate that the accounting information system, does not affect the performance of employees. While theinternal control affect the performance of employees . The data analysis is using Statistical Package for Sosial Science (SPSS). The results show that (1) internal control system has significant impact to employee work performance, (2) accounting information system has no significant impact to employee work performance, (3) accounting information system x internal control have posotive significant impact, to employess performanc